Promote or Inhibit: Economic Goal Pressure and Residents' Health - Zhong, Min; Wang, Peng; Ji, Ming; Zeng, Xi-Hao; Wei, Hong-Xiang (Frontiers in Public Health, 2021)
This paper aimed to identify the relationship of economic growth target pressure and residents' health by applying panel fixed effects model, Sobel-Goodman mediation effects test and regulatory effects model to inland provinces of China. The empirical results verify that the economic growth target pressure of region reduces the level of residents' health.Morever, the effect in developing regions is significantly stronger than that in developed regions, and the effect in the northern region is significantly stronger than that in the southern region. The mediation effects test found that economic growth target pressure has led to a promotion in PM2.5 concentration and an increase in the output of industrial solid waste, thereby constrain residents' health. Regulatory effects model highlight that enhancing public awareness could weaken the negative impact of economic growth target pressure on residents' health, while the expansion of industrial production will aggravate the negative impact.